2019
DOI: 10.1093/mnras/stz2439
|View full text |Cite
|
Sign up to set email alerts
|

Search for neutron star binaries in the Local Group galaxies using LISA

Abstract: We discuss the prospects of LISA for detecting neutron star binaries (NSBs) in the local group galaxies such as LMC and M31. Using the recently estimated merger rate 1540 Gpc −3 yr −1 and inversely applying the conventional arguments based on the Bband galaxy luminosities, we estimate the frequency distributions of NSBs in the local galaxies. We find that, after 10 year observation with its current design sensitivity, LISA might detect ∼ 5 NSBs both in LMC and M31 with signal-to-noise ratios larger than 10. So… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The detection of GW170817 and the selection of LISA as ESA's third L-class mission in January 2017 has led to recent interest in LISA DNSs sources. Seto (2019) estimated the frequency distribution of DNSs in local group galaxies by extrapolating the comoving volumetric DNS merger rate inferred from GW170817. Kyutoku et al (2019) demonstrated that LISA-informed observations can enhance the efficiency of radio pulsar searches with the Square Kilometre Array (SKA).…”
Section: Introductionmentioning
confidence: 99%
“…The detection of GW170817 and the selection of LISA as ESA's third L-class mission in January 2017 has led to recent interest in LISA DNSs sources. Seto (2019) estimated the frequency distribution of DNSs in local group galaxies by extrapolating the comoving volumetric DNS merger rate inferred from GW170817. Kyutoku et al (2019) demonstrated that LISA-informed observations can enhance the efficiency of radio pulsar searches with the Square Kilometre Array (SKA).…”
Section: Introductionmentioning
confidence: 99%
“…Black hole and neutron star binaries are stronger GW emitters compared to DWDs, but a minimum mass of 10 9 M is required for a host (Artale et al 2019). This implies that they should be expected only in the most massive satellites like the Magellanic Clouds (Andrews et al 2019;Lau et al 2020;Seto 2019). Extending our model to these binaries can improve the predicted number counts and the distance horizon for applicability of the method, although it may not improve the accuracy because double black hole and neutron star binaries are more sensitive to the metallicity assumtion than DWDs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although black hole and neutron star binaries are stronger GW emitters in the LISA band compared to DWDs, their rates are expected to be at least three orders of magnitude lower in the Milky Way and only a few sources are predicted to be detectable in nearby massive satellites (e.g. Andrews et al 2019;Lau et al 2020;Sesana et al 2020;Seto 2019).…”
Section: Introductionmentioning
confidence: 99%